Teacher Innovation in Utilizing Learning Technology - Saiful Anwar; Alwi ‘Ainurrofiq; Maulana Paramaditya Ananta (NAJAHA, 2025)
Educational technology is considered a bridge to facilitate the educational process in the pandemic era to achieve the desired goals. So this research aims to analyze the use of learning technology carried out by teachers to innovate with new models or methods in learning. The research method used is qualitative. Data collection was carried out by observation and interviews. The analysis technique uses condensation, presentation, and conclusion. The results of this study are innovations carried out by teachers, including the development of the learning process from home. This indicates that teachers have tried to provide effective learning even though it is done online or remotely. Apart from that, there is also collaboration between teachers and parents, which shows the importance of cooperation between schools and parents in supporting students' learning process. Using internet based learning media is also one of the innovations, where teachers use information and communication technology to provide interactive and exciting learning material for students. Thus, these innovations help increase learning effectiveness and ensure educational continuity amidst unusual conditions such as the pandemic.